INTEGRATED PEST MANAGEMENT OF POTATO CUTWORM, AGROTIS IPSILON (HUFNAGEL) (Biological Sciences - PJSIR, 2004)
An experiment was conducted at Regional Agricultural Research Station (RARS), Jamalpur, Bangladesh, during the period from November 2000 to March 2001 to find out the effective management strategy in controlling potato cutworm, Agrotis ipsilon in the field. The integration of different cultural, biological and chemical management practices showed significant effect on cutworm infestation than the control plots. The lowest percentage of infested tuber by number and weight was observed from the plots treated with hand picking + two irrigation + one spray of Dursban + perching and its yield was also highest. It might be considered as an integrated pest management (IPM) package for combating the cutworm on potato.